Long‐term survival and preprocedural predictors of mortality in high surgical risk patients undergoing percutaneous mitral valve repair. Issue 3 (13th August 2015) - Triantafyllis, Andreas S.; Kortlandt, Friso; Bakker, Annelies L.M.; Swaans, Martin J.; Eefting, Frank D.; van der Heyden, Jan A.S.; Post, Martijn C.; Rensing, Benno W.J.M.
Abstract : Objectives: To evaluate long‐term survival in high surgical risk patients undergoing percutaneous mitral valve repair (MVR) using the MitraClip ® system and to identify preprocedural predictors of long‐term mortality. Background: Data for long‐term survival and preprocedural predictors of mortality after percutaneous MVR in high surgical risk patients are sporadic. Methods: From January 2009 to April 2013, 136 consecutive high surgical risk patients, with symptomatic moderate‐to‐severe or severe mitral regurgitation (MR), underwent percutaneous MVR using the MitraClip system. Cardiac and overall survival was determined at one and 2 years postprocedure. Univariate and multivariate analysis was performed to identify preprocedural predictors of long‐term mortality. Results: One year postprocedure, cardiac and overall survival was 86.7% and 84.6%, respectively and at 2 years cardiac and overall survival was 77.7% and 74.8%, respectively. In univariate analysis advanced age, lower body mass index, impaired renal function, elevated levels of log‐N‐terminal‐pro‐brain‐natriuretic‐peptide (log‐NTproBNP), poor performance in functional tests (New York Heart Association (NYHA) class) and high logistic Euroscore (LES) and Society of Thoracic Surgeons (STS) score were identified as preprocedural predictors of long‐term cardiac mortality. In multivariate analysis preoperative NYHA class III and IV, elevated levels of log‐NTproBNP and advanced age predicted long‐term cardiac mortality. Conclusions: Percutaneous MVR using the MitraClip system has favorable long‐term survival rates in high surgical risk patients. Preprocedural NYHA functional class III and IV, elevated log‐NTproBNP levels and advanced age predict higher long‐term cardiac mortality and should be considered during patient selection. © 2015 Wiley Periodicals, Inc.